Tin Box - Konstantina Sofokleous (My University, 2012)
A tin box belonged to the artist’s mother becomes animated for a movie based on traditional children’s songs and acts as an intermission between two performances of a talking doll, and as an interpretation of the music instruments and their improvisation into animation. Super 8 footage from the artist’s personal archive run during the movie.
Tin Box Performance
Keywords: Computer Animation, Stop Motion, Super 8 Compositing